Persepsi Guru terhadap Pentingnya Bahasa Indonesia dalam Pengembangan Komunikasi Anak Usia Dini - Yoke Ferlina; Abd. Khair Amrullah; Yuliana Nurhayati (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study explores teachers’ perceptions of the importance of the Indonesian language in developing communication skills among early childhood learners. As a national language and medium of unity, Indonesian plays a strategic role in children’s linguistic and social growth. The research applied a qualitative descriptive design, using interviews, observations, and documentation with teachers at TK Ar-Raudah in Banjar Regency. Findings reveal that teachers perceive Indonesian as a crucial foundation for enhancing children’s speaking, comprehension, and expressive abilities. The language also supports children’s confidence and social interaction in learning contexts. However, challenges remain, such as the dominance of regional languages and limited teaching resources. Teachers employ strategies combining local and Indonesian languages to build comprehension and comfort. The study concludes that systematic use of Indonesian from early childhood fosters better communication competence and strengthens national identity. Enhancing teacher training and parental involvement is recommended to optimize Indonesian language development in early childhood education.